Management accounting - Lucey, T. (London : DP Publications, 1992)
This text aims to provide a thorough understanding of management accounting and is designed principally for students preparing themselves for professional examinations. It features case studies and a lecturers' support pack. An LPBB edition is available.
Includes index.
oif 19/03/15
Loans
Keywords: Managerial accounting; Management accounting; Accounting; Financial management; Management Planning; Decision making